Reform of the House of Lords: a “parliamentary version of Waiting for Godot”? - Michael PARSONS (E-REA)
After the rapid implementation of phase one of House of Lords reform, plans for further change, or phase two of the reform, have made little progress. While there is agreement that reform is necessary, there are fundamental differences between the upper and the lower chamber as to how this should be achieved, especially concerning the mode of designation of members of the reformed House (appointment or election). The unsettled economic and political environment means that constitutional reform is not top on the agenda. However there have been important changes in the way the semi-reformed House of Lords has operated over the last few years. It has become much more assertive and has assumed a valuable role in preserving individual freedoms and scrutinising the constitutional implications of any proposed legislation. This poses something of a paradox in that it might be argued that the unelected upper chamber has been more concerned to preserve democratic rights than the elected House of Commons. An elected House of Lords would enjoy greater legitimacy in fulfilling this role in particular and in more generally holding the government to account.